Prospective study of modifiable risk factors of arterial hypertension and left ventricular hypertrophy in pediatric patients on hemodialysis - Borzych-Duzalka, Dagmara; Shroff, Rukshana; Ranchin, Bruno; Zhai, Yihui; Paglialonga, Fabio; Kari, Jameela A.; Ahn, Yo H.; Awad, Hazem S.; Loza, Reyner; Hooman, Nakysa; Ericson, Robin; Drożdz, Dorota; et al. (Kidney international. Reports, 2024)
Introduction - Fluid and salt overload in patients on dialysis result in high blood pressure (BP), left ventricular hypertrophy (LVH) and hemodynamic instability, resulting in cardiovascular morbidity. - Methods - Analysis of 910 pediatric patients on maintenance hemodialysis/hemodiafiltration (HD/HDF), prospectively followed-up with 2758 observations recorded every 6-months in the International Pediatric Hemodialysis Network (IPHN). - Results - Uncontrolled hypertension was present in 55% of observations, with 27% of patients exhibiting persistently elevated predialysis BP. Systolic and diastolic age- and height-standardized BP (BP-SDS) were independently associated with the number of antihypertensive medications (odds ratio [OR] = 1.47, 95% confidence interval 1.39-1.56, 1.36 [1.23-1.36]) and interdialytic weight gain (IDWG; 1.19 [1.14-1.22], 1.09 [1.06-1.11]; all P < 0.0001). IDWG was related to urine output (OR = 0.27 [0.23-0.32]) and dialysate sodium (dNa; 1.06 [1.01-1.10]; all P < 0.0001). The prevalence of masked hypertension was 24%, and HD versus HDF use was an independent risk factor of elevated age- and height-standardized mean arterial pressure (MAP-SDS) (OR = 2.28 [1.18-4.41], P = 0.01). Of the 1135 echocardiograms, 51% demonstrated LVH. Modifiable risk factors included predialysis systolic BP-SDS (OR = 1.06 [1.04-1.09], P < 0.0001), blood hemoglobin (0.97 [0.95-0.99], P = 0.004), HD versus HDF modality (1.09 [1.02-1.18], P = 0.01), and IDWG (1.02 [1.02-1.03], P = 0.04). In addition, HD modality increased the risk of LVH progression (OR = 1.23 [1.03-1.48], P = 0.02). Intradialytic hypotension (IDH) was prevalent in patients progressing to LVH and independently associated with predialysis BP-SDS below 25th percentile, lower number of antihypertensives, HD versus HDF modality, ultrafiltration (UF) rate, and urine output, but not with dNa. - Conclusion - Uncontrolled hypertension and LVH are common in pediatric HD, despite intense pharmacologic therapy. The outcome may improve with use of HDF, and superior anemia and IDWG control; the latter via lowering dNa, without increasing the risk of IDH.